Penentuan Produksi Kerajinan Gerabah Guci Menggunakan Metode Fuzzy Mamdani - Sunaryo, Azzahra Rahmawati; Hastono, Tri; Abelia, Nevanda (Journal Software, Hardware and Information Technology, 2024)
Jar crafts are works of art that are very popular. Jar crafts are also very useful, whether as room decoration or as storage containers. Manufacturers often have difficulty determining the optimal production number of jars. Mamdani fuzzy logic in this research is used to solve problems. The data obtained was processed manually or using Matlab R2019b. This research aims to determine the amount of production using inventory, demand and production variables. In the Mamdani method, to get results, the following stages are required: (a) Fuzzification, (b) Application of the implication function, (c) Rule composition, (d) Defuzzification using the centroid method. From the results of calculations using the Mamdani fuzzy method, the optimum production amount was 83.73.